Status of aspergillosis and sea fan populations in Curaçao ten years after the 1995 Caribbean epizootic - Nugues, M. M. (2006)
In 1995, a survey of sea fan corals was conducted in Curaçao during a Caribbean-wide outbreak of the sea fan disease aspergillosis. The survey was repeated in 2005 using the same methodology and identical sites to examine changes in sea fan populations 10 years after the initial epizootic. Necrotic lesions typical of aspergillosis were present on as many sea fans in 2005 as in 1995 (mean ± SE: 52 ± 6 vs 43 ± 10%). The disease also showed no significant variation in virulence (9.6 ± 1.2 vs 8.8 ± 1.0% tissue loss per diseased colony). However, the average number of sea fan colonies per 10 m2 decreased from 2.7 ± 1.1 to 0.7 ± 0.2 over the 10-year period, a decline of almost 75%. This decrease occurred for all colony sizes, but was more pronounced among small colonies, resulting in an overall trend of domination by large colonies. These results support that aspergillosis can have a significant, long-term impact on sea fan population size and structure. The continued presence of the disease in 2005 could be contributing to reduced recruitment and/or selective mortality among the smallest colonies. This study provides no indication that host resistance against aspergillosis could reverse the decline of Caribbean sea fan corals. Rev. Biol. Trop. 54 (Suppl. 3): 153-160. Epub 2007 Jan. 15.